Topics in Several Complex Variables: First USA-Uzbekistan Conference on Analysis and Mathematical Physics, May 20-23, 2014, California State University, Fullerton (ProtoView, 2016)
Among the topics are pseudo-holomorphic discs and symplectic structures in Hilbert space, the pluri-polarity of graphs of quasi-analytic functions of several complex variables, integral formulas for some matrix domains, the holomorphic continuation of functions in domains with singular boundaries, the uniqueness property for Gonchar quasi-analytic functions of several variables, and an analogue of Lelong's theorem for m - wsh functions. (© Ringgold, Inc., Portland, OR)